Plan de negocios para la creación de una empresa productora y comercializadora de leche saborizada. - Bonilla Cañizares, Cristian Oswaldo (2023)
Talking about the dairy sector in the country, and especially in the central mountains, is a fundamental part of the economy of the provinces in the sector. The province of Cotopaxi is recognized for its rich agricultural and livestock tradition, the dairy sector occupies an important place in the generation of resources and the creation of jobs for this sector. The dairy sector in the province of Cotopaxi is characterized by the diversity of producers, from family units to large companies. Over time this sector has been developing with best practices, adopting innovative technologies, thus increasing the productivity and efficiency of the producers. producers. Cow's milk is one of the most consumed foods in the world, but with new nutrition and food trends, this consumption has been decreasing, as has the increase in the number of lactose intolerant people, the chocho that turns out to be A legume from the Andes region is a substitute for cow's milk and contains enough protein to satisfy the diet. That is why, seeing the business opportunity that this sector offers, the creation of a plant that produces and markets flavored lupine-based milk drinks is proposed, the objective of which is to structure a business plan for the creation of a company that produces and marketing of flavored milk, we carried out a market study to observe the acceptance of this product, obtaining 70%, and consuming it at least once a week. The company will have an installed capacity of 3,840,000.00 liters of milk annually, which represents 115,200.00 units of ½ liter that will be produced in the plant in the year, at an introductory price of 1.27 ctv., our company will have an IRR of 11% and a NPV of $8,456.79, seeing that the company is viable.